Meta-synthesis of the motherhood-related needs of women with multiple sclerosis - Elaheh Mansouri Ghezelhesari; Abbas Heydari; Hosein Ebrahimipour; Mohammad Ali Nahayati; Talat Khadivzadeh (BMC, 2024)
Abstract Background The treatment of multiple sclerosis, an autoimmune disease that predominantly affects women of reproductive age, has undergone considerable advancements. Nevertheless, their unique needs, particularly those related to motherhood, continue to be disregarded. This study aims to ascertain the needs of women diagnosed with MS about motherhood. Methods Using the Noblit and Hare methods, meta-synthesis research was conducted on 10 qualitative studies. The relevant studies were obtained by conducting a comprehensive search using keywords in the PubMed, Scopus, Web of Science (ISI), and ProQuest databases without any time limitations until June 2023. The CASP checklist was used to assess the quality of the articles, while the technique of Brown and Clark (2006) was utilized for data synthesis. Results Four key themes emerged from this meta-synthesis, highlighting the significance of a support system, psychoeducational counseling, knowledge promotion, and continuous, comprehensive, and unique care. Conclusion Identifying the needs of women diagnosed with MS and addressing these needs concerning motherhood can enhance the quality of services rendered and enhance women's contentment with their choice to embark on motherhood. Furthermore, recognizing these needs during subsequent stages can be utilized in formulating tailored programs catering to this specific cohort of women.